Digital leadership of school principals to improve the quality of learning in the industrial revolution era 4.0 - Muhammad Rasyid Ridho; Bambang Budi Wiyono; Mustiningsih (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
The current globalization has also given rise to new leadership styles, including digital leadership. Digital leadership style is one alternative approach school principals use to improve the quality of learning by utilizing technological sophistication. This study aims to determine the strategy, implementation, and obstacles in the digital leadership of school principals to improve the quality of learning in the era of the Industrial Revolution 4.0 at SMA Muhammadiyah 1 Malang and MA Al Irtqio' Malang City. This study uses a qualitative approach with a multi-site study design conducted at SMA Muhammadiyah 1 Malang and MA Al Irtiqo' Malang City. Data collection techniques include observation, interviews, and documentation. The results showed that in his strategy, the principal sought to conduct technology-based learning media training for educators, seeking the ability of educators to utilize technology. The implementation is done by striving to learn using digital media, completing technology-related facilities, collaborating with various parties, and integrating technology into school administration. The obstacles are children's different backgrounds, conventional teaching, and internet network connectivity.